VESICULAR-ARBUSCULAR MYCORRHIZAL STATUS OF PLANT SPECIES IN THE PEAT SWAMP FOREST OF SETIA ALAM JAYA, SEBANGAU, CENTRAL KALIMANTAN - Suciatmih Suciatmih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2003)
In order to describe the vesicular-arbuscular mycorrhizal (VAM) status of plants growing on peat soil, a study was carried out in the peat swamp forest of Setia Alam Jaya in Sebangau, Central Kalimantan. Out of 146 plant root samples belonging to 48 plant species from 25 families examined, all plants colonized by VAM fungi namely 14 (29.2%) high level, 32 (66.7%) medium level, and 2 (4.1%) low level respectively.